Failures and reoperation in fixed prosthesis -Systematic Review- - Amine, CHAFII; Abdallah, MOUHIBI; Abderrhman, ANDOH (International Journal of Dental Research, 2021)
Our systematic review is made in view of the absence of studies dealing with failures and reoperations which encompassed all types of dento-supported fixed prosthetic restorations and aims to study prosthetic failures that could be encountered in fixed dento-supported prosthesis and the solutions to remedyOver the past two centuries, considerable progress has been made under the leadership of many scientists who have developed materials and techniques, with the aim of improving the quality of care and improving ergonomics.In short, in fixed prosthesis, failures have particularly serious consequences and can occur at all levels involved for these restorations. They can happen at any time.This is how we were able to note the influence of certaine variable on the success and durability of the treatments, which did not depend only on the skill and precision used during prosthetic development, such as the location, arch, preparation design, number of abutments, type of material used, bonding material, surface treatment and technologies used.So the choice of restorative materials was a decisive factor that had to be the result of a careful study of the different materials available depending on the clinical situation, in order to increase their longevity and therefore reduce the risk of failure.Â Â Â